ANALISIS MENU ENGINEERING DALAM UPAYA MENINGKATKAN PENJUALAN MAKANAN DI DEUS CAFE CANGGU, KUTA UTARA BALI - Polikarpus.N, Pondang; Suthanaya, I Putu Bagus; Suryani, Putu Evi (Universitas Triatma Mulya, 2022)
This research is menu engineering analysis in an effort to increase food sales at Deus Cafe Canggu. The formulation of the problem raised in this study is how to apply menu engineering analysis, how to analyze menu based on menu engineering, and how to strategy in increasing food sales at Deus Cafe Canggu. This research was conducted using qualitative data and quantitative data sourced from primary data obtained from interviews and observations, as well as secondary data obtained from companies in the form of menu lists, selling prices, food costs, and history of sales. The analysis method used in this study is menu engineering and the object under study is the type of salad dish, main course, light meals, and kids menu. Based on the results of the analysis carried out, it can be concluded that there are 8 items (26.67%) types of dishes for the star group, 10 items (33.33%) types of dishes for the plow horse group, 6 items (20.00%) types of dishes for the puzzle group, and 6 items (20.00%) types of dishes for the dog group. The decisions and follow-up actions taken by management in increasing food sales are maintaining the quality and selling price of food for the star group, controlling food costs and increasing the selling price of food for the plow horse group, revising the menu and promoting for the puzzle group, evaluating the menu and deleting the menu. for the dog group.